Peningkatan Peran Kelompok Perempuan melalui Pembibitan Mangrove untuk Mendukung Keberlanjutan Ekonomi Lokal Masyarakat Pesisir - Eka Lisdayanti; Fadli Afriandi; Rahmawati Rahmawati (Jurnal Pemberdayaan Masyarakat, 2024)
Utilization and management of mangroves in the Mangrove Ecotourism Area has been carried out since 2018. Mangroves are one of the unique ecosystems in the coastal area and have been widely used by the community. This community service activity aims to increase the role of women's groups in the utilization and preservation of coastal ecosystems. Given that Aceh Jaya is one of the locations in Aceh Province that already has a mangrove area of ​​± 300 ha. This community service uses a mixed field-based method, with direct observation, open interviews, and structured discussions with managers, group members, and the community which began in July and will end in December 2024. The results of the community service show that fishing, crab, and tourism activities are the main activities in the utilization of mangroves by the community around the eco-tourism area. Although previously women had been indirectly involved in the utilization of mangroves, with this community service activity, women's group members are more active in participating directly in each stage. The increase in the role of female members involved can be seen in the increase in the percentage of knowledge and participation in planting. This service provides input into the management pattern of mangrove ecosystems, especially in nurseries, with the division of tasks and responsibilities, the activeness of members in each stage is not impossible to continue to improve.